RISK OF EATING DISORDER AND BODY SHAPE CONCERN AMONG UNDERGRADUATE NURSING STUDENTS - Shrestha, Ashmita; Kumari Maharjan, Sapana; Mehta, Mamata; Pradhan, Rita; Dhungana, Sudarshan; Joshi, Puspal (Journal of Chitwan Medical College, 2024)
Background: Eating disorders (anorexia nervosa, bulimia nervosa and binge eating) are mental illness associated with severe disturbances in people’s eating behavior which results in both psychological and social impairments. Body image dissatisfaction might be an important predictor of increased incidence of eating disorder. This study aimed to assess the risk of eating disorder and body shape concern among undergraduate students at selected nursing colleges, Morang. Methods: A descriptive cross-sectional design was conducted among 288 undergraduate nursing students selected by non-probability convenient sampling technique. Data was collected through self-administered method using EAT-26 and BSQ-34 standard tool. The obtained data were analyzed by descriptive and inferential statistics using SPSS version 16 software. Results: Among 288 nursing students, majority (83%) of them had no risk while (17%) had risk of eating disorder. Similarly, majority (62.2%) of them had no concern with body shape, (19.8%) had mild concern, (12.2%) had moderate concern and (5.9%) had marked concern. There is a statistically significant association between the risk level and selected socio demographic variables like religion (P= 0.01*), weight (P=0.009*), BMI (P= 0.001*). Conclusions: Majority of the students had no risk while very few students had risk of eating disorder. Almost half of the nursing students had mild to marked concern about body shape which can entice eating disorder.